Effect of Saturation on Soil Subgrade Strength (International Journal of Innovative Research in Engineering & Management, 2022)
Pavements are made up of many  materials. The qualities of the resulting pavement are  determined by these materials, their related properties, and  their interactions. As a result, knowing these materials,  how well they are classified, and how they operate is  critical to understanding pavement. The materials used in  highway building are of particular interest to highway  engineers. This necessitates not only a detailed knowledge  of the soil and aggregate parameters that influence  pavement stability and durability, as well as the binding  elements that may be applied to improve these pavement  characteristics. Soil is a mass or deposition of earth  material that may be easily mined using heavy machinery  in the field or decomposed by mild mechanical methods in  the laboratory, generated organically from mineral  weathering or decay of plants. This research deals with the effect of moisture on the  strength of soil. Six different soil samples are selected for  the experimentation. These samples are classified in to  various types. This classification was done based on sieve  analysis, liquid limit, plastic limit, plastic index and  plasticity chart. The samples were classified as ML, CL,  SC and SM. The strength of soil is measured through its  CBR value. The CBR value was calculated for unsoaked  condition and soaked condition for 1, 2,3 and 4 days and  these values were compared. The values of CBR show  there is decrease in CBR for all the soil samples.
Keywords: CBR; ML; CL; SC; SM